The South African security predicament: making sense of the objective realities - Esterhuyse, Abel (Scientia Militaria - South African Journal of Military Studies, 2021)
This article reflects an effort to make sense of the objective realities of the South African security predicament. The objective realities on the security agenda are rooted in the practical reality of experience and are open for public discussion, debate and speculation. These realities are informed by the threats facing South Africans on a daily basis. Government provides security with subjective content to the extent that political power demarcates the threat agenda, prioritises the items on the threat agenda, and foots the security bill. Since the creation of the Union in 1910, South Africa has had to find a balance between the security realities emanating from three key security domains – irrespective of the ruling entity: security threats from outside Africa, those threats facing the country from within Africa, and security threats from within the borders of South Africa. The article aims at a scholarly demarcation of some of the most critical, important, and key features of the South African security agenda using these three domains as a framework for discussion. On a secondary level, the discussion also critically reflects on the ability of the human security paradigm to address the South African security predicament.